Case Studies and Lower-bound Capacity Prediction of Precast Jacked Piles Installed in the Philippines - Buensuceso, Benjamin III (Himpunan Ahli Teknik Tanah Indonesia, 2025)
This research compiles multiple case studies of a variety of precast jacked pile lengths and slenderness ratios tested with high-strain dynamic load pile tests (HSDPT) in the Luzon region of the Philippines. This allows for the exploration of the relationship between pile slenderness ratio, HSDPT ultimate capacity, and final jacking force (Pjack), the evaluation of existing empirical lower-bound predictions of ultimate capacity that utilize slenderness and Pjack, and the establishment of new lower-bound predictive formulas best-suited for the collected data. Four case studies are presented, with a total of 135 jacked, square, precast piles tested with HSDPTs included. Slenderness ratios in the four case studies ranged from 5.11 to 63.8. The ratio of an ultimate capacity measured in the HSDPT to Pjack, also called pressure ratio, was found to be a function of the slenderness ratio, with pressure ratios generally rising above 1.0 for piles with slenderness ratios above 30. Actual pressure ratios and ultimate capacities measured were also compared to two previously established empirical lower-bound predictions, with 93% and above of actual pressure ratios and capacities above those predicted. Two alternative lower-bound pressure ratio formulas that are a function of slenderness are also proposed, particularly to deal with low-slenderness piles in the database (L/D < 10) that cannot be adequately modeled by existing formulas.